Bi-component inorganic oxide nanofibers from gas jet fiber spinning process. Issue 127 (14th December 2015) - Ghosh, Monoj; Jana, Sadhan C.
Abstract : Bi-component semiconducting metal oxide nanofibers with core–shell and side-by-side morphologies in mesoporous or solid cylindrical shapes are produced by gas-jet fiber process. Abstract : Nanometer size bi-component semiconducting metal oxide (SMO) fibers with tailored morphology are fabricated via a Gas Jet Fiber (GJF) spinning process using a polymer template in conjunction with conventional precursor sol–gel chemistry. The GJF process is capable of producing SMO fibers with morphological forms such as mesoporous or solid cylindrical core–shell and side-by-side.